Local structural analysis of erbium-doped tellurite modified silica glass with x-ray photoelectron spectroscopy. (19th June 2019) - Ahmad Kamil, Suraya; Chandrappan, Jayakrishnan; Portoles, Jose; Steenson, Paul; Jose, Gin
Abstract: Ultrafast laser plasma doping (ULPD) is a recently developed technique that enables the blending of femtosecond laser produced plasma from a TeO2 (target) based glass with a SiO2 (substrate) without or minimum phase separation to form a silicate glass. The background oxygen gas pressure plays a major role in ULPD as it directly impacts the plasma plume characteristics, resulting in lower erbium doped tellurite modified silica (EDTS) thickness and refractive index at higher process gas pressure. X-ray photoelectron spectroscopy (XPS) used in this study to analyse the formation of EDTS and local bonding environment of its constituents. This report confirms the presence of both target materials and SiO2 in the resulting EDTS films. XPS of O 1 s core, confirms that bridging oxygen (BO) is more dominant compared to non-bridging oxygen (NBO) in the EDTS glass network, and the amount of BO is more stand out for higher gas pressures when the glass modifiers are relatively smaller in concentration. Our study revealed the nucleation Te and Er to form metal nanoparticles in glass under certain preparation conditions/doping concentration which were previously undetected using other experimental techniques. It is important to control this nanoparticle formation in engineering EDTS for photonic device applications.